The Effectiveness of Psychodrama Technique Group Guidance to Increase High School Student’s Confidence - Fatimah Febri Yani; Agus Basuki (AL-ISHLAH: Jurnal Pendidikan, 2023)
Self-confidence is an essential attribute for students as it enables them to engage in the learning process, take calculated chances, and pursue their goals without being hindered by concerns about the outcomes. There is a pressing need to implement measures aimed at enhancing students' self-confidence, as it is evident that not all students possess this attribute. The objective of this study is to assess the efficacy of psychodrama technique group supervision in enhancing students' self-confidence. The present study employs a pre-experimental approach known as the one-group pretest-posttest design. The target population for this research consists of 30 students enrolled in Class X IPS 1. The sample was taken by purposive sampling which involved 8 students. The research data was collected using a measurement scale, the results of the validity test of the students' self-confidence scale items were between 0.000-0.050 while the Cronbach’s alpha reliability test was 0.807. The results show that there are several conclusions, namely: 1) the self-confidence experienced by students can increase from low to high. 2) hypothesis testing in this study using the paired sample t-test test technique, the results of the data obtained by Asymp.Sig. (2-tailed) of 0.000 0.05, which means that it is significant, psychodrama technique group guidance has been proven effective in increasing students' self-confidence because it uses psycodrama techniques in group situations where students can interact with each other. Limitations in this study require a larger sample for more accurate analysis results. Further research self-confidence can be done on improving psychodrama technique primary on the role, task and dialogue.